Revealing New Insights: Preserving Islamic Manuscripts in Eastern Indonesia - Maulani, Abdullah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
In the 19th century, the influence of scholars from Sulawesi residing in the Haramayn (Mecca and Medina) became even more vibrant, contributing to the religious life in the Sulawesi Islands. This was marked by their return to their hometowns and the establishment of various Islamic educational centers. One of them was Shaykh ‘Abd al-Majīd bin ‘Abd al-Hayy al-Bugisi al-Būnī (d. 1878). He was one of the scholars from Pompanua, Bone Regency, who had Islamic education activities in Haramayn and returned to South Sulawesi in 1860. Unfortunately, today, his manuscript collections are in terrible condition. Yet, his works serve as authentic evidence of how Islam flourished rapidly in South Sulawesi in the 19th century through the networks of scholars from the Middle East and Africa. Therefore, on 2-28 February 2023, The Dreamsea Program carried out the preservation of the manuscript collection of Shaikh Abdul Majid to save the forgotten Islamic treasure in the Eastern Indonesia region.